Recent Trends in Non-Surgical Periodontal Care for the General Dentist - A Review - Arpita, R; Swetha, JL; Babu, MR; Sudhir, R (Bangladesh Journal of Dental Research & Education, 2014)
The management of periodontal defects has been an ongoing challenge in clinical periodontics. In the recent past, attention has been focused more on regenerative and reconstructive therapies i.e. bone grafts, guided tissue regeneration, root conditioning, polypeptide growth factors, rather than on respective therapies. These therapeutic measures are shown to be limited in the predictability of healing and regenerative response in the modem clinical practice because oral environment presents several complicating factors that border regeneration. The 21st century appears to represent a time in history when there is a convergence between clinical dentistry and medicine, human genetics, developmental and molecular biology, biotechnology, bioengineering, and bioinformatics, resulting in the emergence of novel regenerative therapeutic approaches and focusing mainly on non surgical modalities. The purpose of this article is to provide a review of the various non surgical therapies in use today. Future direction in this ever-changing field is also discussed. Techniques currently in use are reviewed and evaluated. They include Probiotics, Ozone therapy, Photodynamic therapy, Gene therapy, RNA interference, Nanotechnology, Perioprotect, TIPS & BOST. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20254 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 78-82